Pentingnya Literasi dan Transformasi Digital untuk Pembelajaran Pada SMP Negeri 1 Sarirejo - Dilasari, Aranta Prista; Ani, Heti Nur; Salukh, Agustinus; Hakim, Mesra Berlyn (-, 2025)
The purpose of this study was to improve literacy skills and technological skills in students at SMP Negeri 1 Sarirejo. The methods used in this study were observation and interviews. The technique used was descriptive qualitative. Based on the results of the study, overall the implementation of the program went well. However, there were programs that could not be implemented due to financial constraints from the school. However, the researcher was able to replace the program with activities that minimized costs.